Penilaian terhadap penentuan awal Ramadhan dan Syawal oleh Institusi Islam di Aceh menurut hadith Nabi / Faisal Yahya - Faisal, Yahya (2017)
There are several methods in setting the first ramadan and eid day used by some islamic institutions in Aceh, so the implementation of it is always be held in different dates. This study was conducted to analyze the method used in Islamic institution in Aceh in defining the first of Ramadan and Syawal. This study aim to assess the methods used by Islamic institution in Aceh in defining the first Ramadan and Syawal in accordance to the prophetic traditional (Hadis Nabi). In order to answer the objective, the writer conducted the interview with the Islamic institution that prescribed the first Ramadan and Syawal. The data were analyzed by using inductive, deductive and comparative analysis. The result found that there were three methods used in defining the first Ramadan and Syawal by Islamic institution in Aceh, which are; the first, hisab khamasi method by using bulen tren and bulen ek, and by completing 30 days of Ramadan throughout the year. The second, ru’yah hilal bi fiʻli by using matla eight degree lengthwise. The third, imkan alru’yah method by matla’ wilayah al-hukm Ministry of Religion of Republic Indonesia. In addition, there also discovered here are some masjid institutions that follow the provision of Saudi Arabian Kingdom and they did not notice any other method. The result indicated by hisab khamasi method and its application has contradiction with the hadith of Prophet Muhammad SAW. While the institution that used ru’yah hilal bi fiʻli method by using matla eight-degree lengthwise, conducted textual comprehension toward hadith of prophet by not using current scientific method. Whereas institution that follow the Saudi Arabian Kingdom provision was not supported by al-Qur’an and hadith. This study is expected to give the perception and discourse towards the Republic Indonesia Ministry of Religion in order to synchronize the first Ramadan and Syawal in Indonesia, and provide the information for Acehnese in fulfilling fasting month and welcoming the eid day.